Bibliometric analysis of gaps in research on asbestos-related diseases: declining emphasis on public health over 26 years. Issue 7 (25th July 2018) - Lin, Ro-Ting; Soeberg, Matthew John; Chien, Lung-Chang; Fisher, Scott; Takala, Jukka; Lemen, Richard; Driscoll, Tim; Takahashi, Ken
Abstract : Objectives: The global burden of asbestos-related diseases (ARDs) is significant, and most of the world's population live in countries where asbestos use continues. We examined the gaps between ARD research and suggestions of WHO and the International Labour Organization on prevention. Methods: From the Web of Science, we collected data on all articles published during 1991–2016 and identified a subset of ARD-related articles. We classified articles into three research areas—laboratory, clinical and public health—and examined their time trends. For all and the top 11 countries publishing ARD-related articles, we calculated the proportions of all ARD-related articles that were in each of the three areas, the average rates of ARD-related articles over all articles, and the average annual per cent changes of rates. Results: ARD-related articles (n=14 284) accounted for 1.3‰ of all articles in 1991, but this had declined to 0.8‰ by 2016. Among the three research areas, the clinical area accounted for the largest proportion (65.0%), followed by laboratory (26.5%) and public health (24.9%). The public health area declined faster than the other areas, at −5.7% per year. Discrepancies were also observed among the top 11 countries regarding emphasis on public health research, with Finland and Italy having higher, and China and the Netherlands lower, emphases. Conclusions: There is declining emphasis on the public health area in the ARD-related literature. Under the ongoing global situation of ARD, primary prevention will remain key for some time, warranting efforts to rectify the current trend in ARD-related research.